Neurocognitive outcomes of children exposed to and living with HIV aged 3–5 years in Kilifi, Kenya - Chongwo, Esther Jebor; Wedderburn, Catherine J.; Nyongesa, Moses Kachama; Sigilai, Antipa; Mwangi, Paul; Thoya, Janet; Odhiambo, Rachel; Ngombo, Katana; Kabunda, Beatrice; Newton, Charles R.; Abubakar, Amina (Frontiers in Reproductive Health, 2023)
Globally, 1.7 million children are living with HIV, with the majority of them residing in sub-Saharan Africa. Due to reduced rates of vertical transmission of HIV, there is an increasing population of children born to HIV-infected mothers who remain uninfected. There is a growing concern around the development of these children in the antiretroviral therapy era. This study examined the neurocognitive outcomes of children who are HIV-exposed infected (CHEI), HIV-exposed uninfected (CHEU) and HIV-unexposed uninfected (CHUU) and explored the relationship between child neurocognitive outcomes and child’s biomedical and caregivers’ psychosocial factors. CHEI, CHUU and CHEU aged 3-5 years and their caregivers were recruited into the study. Neurocognitive outcomes were assessed using a validated battery of assessments. One-way analysis of variance and covariance (ANOVA and ANCOVA) were used to evaluate differences among the three groups by neurocognitive outcomes. Linear regression models were used to investigate the association between child neurocognitive outcomes and biomedical factors (nutritional status, HIV disease staging) and caregivers’ psychosocial factors (symptoms of common mental disorders [CMDs] and parenting behaviour). The study included 153 children and their caregivers: 43 (28.1%) CHEI, 52 (34.0%) CHEU and 58 (39.9%) CHUU. ANOVA and ANCOVA revealed a significant difference in cognitive ability mean scores across the child groups. Post-hoc analysis indicated that CHEU children had higher cognitive ability mean scores than the CHUU group. Better nutritional status was significantly associated with higher cognitive ability scores (β=0.68, 95% CI [0.18-1.18], p=0.008). Higher scores of CMDs were negatively associated with inhibitory control (β= -0.28, 95% CI [-0.53-0.02], p=0.036). While comparing HIV stages 2 and 3, large effect sizes were seen in working memory (0.96, CI [0.08-1.80]) and cognitive ability scores (0.83 CI [0.01-1.63]), indicating those in stage 3 had poor performance. Neurocognitive outcomes were similar across CHEI, CHEU and CHUU, although subtle differences were seen in cognitive ability scores where CHEU had significantly higher cognitive mean scores than the CHUU. Well-designed longitudinal studies are needed to ascertain these findings. Nonetheless, study findings underscore the need for strategies to promote better child nutrition, mental health, and early antiretroviral therapy initiation.